The self- and foreign-absorption continua of water vapor by cavity ring-down spectroscopy near 2.35 μm. Issue 27 (21st July 2015) - Mondelain, D.; Vasilchenko, S.; Čermák, P.; Kassi, S.; Campargue, A.
<x xml:space="preserve">Abstract</x> Water vapor self and foreign continuum absorption cross sections are measured with unprecedented accuracy around 2.35 μm using high sensitivity CRDS.